Introduction to Insurance Mathematics Technical and Financial Features of Risk Transfers - Olivieri, Annamaria; Pitacco, Ermanno; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This second edition expands the first chapters, which focus on the approach to risk management issues discussed in the first edition, to offer readers a better understanding of the risk management process and the relevant quantitative phases. In the following chapters the book examines life insurance, non-life insurance and pension plans, presenting the technical and financial aspects of risk transfers and insurance without the use of complex mathematical tools.   The book is written in a comprehensible style making it easily accessible to advanced undergraduate and graduate students in Economics, Business and Finance, as well as undergraduate students in Mathematics who intend starting on an actuarial qualification path. With the systematic inclusion of practical topics, professionals will find this text useful when working in insurance and pension related areas, where investments, risk analysis and financial reporting play a major role.
1 Risks and Insurance -- 2 Managing a Portfolio of Risks -- Life Insurance: Modeling the Lifetime -- 4 Life Insurance: Pricing -- 5 Life Insurance: Reserving -- 6 Reserves and Profits in a Life Insurance Portfolio -- 7 Finance in Life Insurance: Linking Benefits to the Investment Performance -- 8 Pension Plans: Technical and Financial Perspectives -- 9 Non-life Insurance: Pricing and Reserving -- Index.
Keywords: Game theory; Finance; Statistics .; Game Theory, Economics, Social and Behav. Sciences; Finance, general; Statistics for Business, Management, Economics, Finance, Insurance